CuInS2Photocathodes with Atomic Gradation-Controlled (Ta,Mo) x(O,S) yPassivation Layers for Efficient Photoelectrochemical H2Production - Chae, Sang Youn; Kim, Yoolim; Park, Eun Duck; Im, Sang Hyuk; Joo, Oh Shim (ACS Applied Materials and Interfaces, 2021)
An atomic gradient passivation layer, (Ta,Mo)x(O,S)y, is designed to improve the charge transportation and photoelectrochemical activity of CuInS2-based photoelectrodes. We found that Mo spontaneously diffused to the a-TaOx layer during e-beam evaporation. This result indicates that the gradient profile of MoOx/TaOx is formed in the sublayer of (Ta,Mo)x(O,S)y. To understand the atomic-gradation effects of the (Ta,Mo)x(O,S)y passive layer, the composition and (photo)electrochemical properties have been characterized in detail. When this atomic gradient-passive layer is applied to CuInS2-based photocathodes, promising photocurrent and onset potential are seen without using Pt cocatalysts. This is one of the highest activities among reported CuInS2 photocathodes, which are not combined with noble metal cocatalysts. Excellent photoelectrochemical activity of the photoelectrode can be mainly achieved by (1) the electron transient time improved due to the conductive Mo-incorporated TaOx layer and (2) the boosted electrocatalytic activity by Mox(O,S)y formation.
Keywords: Charge transportation; E beam evaporation; Electrocatalytic activity; Onset potential; Passivation layer; Photo-electrodes; Photoelectrochemicals; Transient time; atomic gradation; CuInS2; passivation layer; photoelectrochemical cell; tantalum oxide